Persistent HPV infection after conization of cervical intraepithelial neoplasia-- a systematic review and meta-analysis - Yueyang Zhang; Zhiwen Ni; Ting Wei; Qingsong Liu (BMC, 2023)
Abstract Objective To systematically evaluate several factors of persistent human papillomavirus (HPV) infection following conization in patients with cervical intraepithelial neoplasia (CIN). Methods PubMed, EMBASE and the Cochrane Library were searched from January 1, 1998 to September 10, 2021. Random-effects models for meta-analyses were used and pooled relative risks with 95% confidence intervals were reported. Literature screening, data extraction, and assessment of the risk of bias in the included studies were conducted independently by two researchers. Data analysis was performed with Stata software, version 12.0. Results A total of 28 studies were included in this study. Meta-analysis revealed that surgical margin and residual disease were positively correlated with persistent HPV infection after conization. Compared with patients infected with other types of HPV, CIN patients with HPV 16 had a higher persistent infection rate (OR = 1.967, 95% CI (1.232-3.140), P < 0.05). Conclusions CIN patients who are postmenopausal, have positive surgical margins and residual lesions, and are positive for HPV 16 are prone to persistent HPV infection after conization.